2020
DOI: 10.3389/fnins.2020.00169
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Prevents Sleep Deprivation-Induced Hippocampal Damage by Upregulation of Sirt1 in the Hippocampus

Abstract: Sleep deprivation (SD) induces hippocampal damage. Hydrogen sulfide (H 2 S) is a neuronal protective factor. Silence information regulating factor 1 (Sirt1) plays an important role in neuroprotection. Therefore, this study was aimed at exploring whether H 2 S meliorates SD-induced hippocampal damage and whether Sirt1 mediates this protective role of H 2 S. We found that sodium hydrosulfide (NaHS, a donor of H 2 S) alleviated SD-generated hippocampal oxidative stress, including increases in the activation of SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
2
13
0
Order By: Relevance
“…Further, it has previously been shown that insomnia can induce hippocampal injury and Nissl substance loss. is prior finding is in good agreement with our results, because it has been shown that sleep deprivation causes hippocampus damage by increasing oxidative stress, eventually leading to neuronal apoptosis and Nissl substance loss in the brain [44,45]. However, we found that treatment with MSZRD attenuated damage to the gastric mucosal and hippocampus.…”
supporting
confidence: 93%
“…Further, it has previously been shown that insomnia can induce hippocampal injury and Nissl substance loss. is prior finding is in good agreement with our results, because it has been shown that sleep deprivation causes hippocampus damage by increasing oxidative stress, eventually leading to neuronal apoptosis and Nissl substance loss in the brain [44,45]. However, we found that treatment with MSZRD attenuated damage to the gastric mucosal and hippocampus.…”
supporting
confidence: 93%
“…In accordance with the iron accumulation, significantly downregulated protein expression of Sirt1, Sirt3 and Nrf2 was observed in the present study, which is consistent with previous studies. 47,48 However, we observed significantly decreased levels of iron and increased protein expression of Sirt1, Sirt3 and Nrf2 in MKD-and LKD-treated SD mice. Of note, the MKD exerted more significant effect than the LKD in increasing Sirt3 and Nrf2.…”
Section: Papermentioning
confidence: 63%
“…Whole brain also shows similar measures of oxidative stress in response to chronic sleep loss [59]. Various antioxidant therapies administered in animal studies across the diverse chronic sleep disruption paradigms mitigate neurobehavioral impairments, mitochondrial injury and apoptosis [55,57,58,60], supporting an active role for oxidative stress in sleep disruption hippocampal responses. It remains unclear, however, how specifically mitochondria and metabolics are challenged by chronic sleep disruption.…”
Section: Trends In Neurosciencesmentioning
confidence: 87%
“…The morphological changes were observed in parallel with reduced basal and maximal oxygen consumption rates in hippocampal, but not cortical, mitochondria after REM sleep deprivation, supporting regional or neuronal differential susceptibility to mitochondrial dysfunction in response to chronic sleep disruption. In support of mitochondrial dysfunction, a number of groups have shown increased oxidative stress (reduced glutathione, increased oxidized: reduced glutathione, increase malondialdehyde) in hippocampal tissue of rats and mice exposed to total sleep deprivation, REM sleep deprivation, and sleep fragmentation [21,46,[55][56][57][58]. Whole brain also shows similar measures of oxidative stress in response to chronic sleep loss [59].…”
Section: Trends In Neurosciencesmentioning
confidence: 99%